Rheumatologic rehabilitation: towards recommendations - S. Maddali Bongi; A. Del Rosso; M. Matucci Cerinic (PAGEPress Publications, 2014)
Rheumatic patients are highly complex and often affected by chronic diseases. Rehabilitation is generally needed for proper management of the underlying disease. This article describes the characteristics of an effective rheumatologic rehabilitation, takes into account data published in international literature, suggests recommendations based on scientific evidence to develop a correct rehabilitation plan for rheumatic patients and proposes the basis to draw up guidelines in the field of rheumatologic rehabilitation.